Some Peculiarities of Hybrid Language "Camfranglais" - Baghana, Jerome; N. Prokhorova, Olga; S.Blazhevich, Yuliya; G.Voloshyna, Tatyana; L. Kuksova, Elena (International Journal of Engineering and Technology, 2018)
The article is devoted to the peculiarities of hybrid language code called "Camfranglais"(CFA), which emerged in large cities as a youth social code and now is rather popular and widely used in Cameroon. The researchers have described and analyzed the causes of CFA occurrence and its social functions in the modern Cameroonian society. The existing terms describing CFA have been analyzed. The authors have studied the morpho-syntactic structures of CFA and the basis of CFA dictionary. The main sources of CFA replenishment and semantic processes that accompany the process of borrowing from other languages have also been defined and considered.Â Â Â
Keywords: Camfranglais; hybrid language; French; English; Pidgin-English; Cameroonian languages; borrowing.